Fracture Mechanics Models for Brittle Failure of Bottom Rails due to Uplift in Timber Frame Shear Walls - Joergen L. Jensen; Giuseppe Caprolu; Ulf Arne Girhammar (Advances in Civil Engineering)
In partially anchored timber frame shear walls, hold-down devices are not provided; hence the uplift forces are transferred by the fasteners of the sheathing-to-framing joints into the bottom rail and via anchor bolts from the bottom rail into the foundation. Since the force in the anchor bolts and the sheathing-to-framing joints do not act in the same vertical plane, the bottom rail is subjected to tensile stresses perpendicular to the grain and splitting of the bottom rail may occur. This paper presents simple analytical models based on fracture mechanics for the analysis of such bottom rails. An existing model is reviewed and several alternative models are derived and compared qualitatively and with experimental data. It is concluded that several of the fracture mechanics models lead to failure load predictions which seem in sufficiently good agreement with the experimental results to justify their application in practical design.